2010
DOI: 10.1590/s0006-87052010000400002
|View full text |Cite
|
Sign up to set email alerts
|

Estimativas de parâmetros genéticos de caracteres relacionados ao vigor de estacas em Lippia alba

Abstract: RESUMOA espécie Lippia alba da família Verbenaceae, aromática e medicinal, é um arbusto nativo com muito vigor e variabilidade genética. O principal interesse dos estudos com esta espécie são os óleos essenciais, cujas funções têm sido comprovadas cientificamente para aplicações nas indústrias de fármacos, cosmética, perfumaria e alimentícia. Apesar desta importância potencial, inexistem pesquisas sobre estimativas de parâmetros genéticos nesta espécie como forma de subsidiar o melhoramento que até o presente … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
3
0
2
Order By: Relevance
“…The broad-sense heritability was calculated by the estimator: h 2 = σ (Alves et al, 2006;Rufino et al, 2010;Rêgo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The broad-sense heritability was calculated by the estimator: h 2 = σ (Alves et al, 2006;Rufino et al, 2010;Rêgo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…From table 1, facilitating the selection of more productive clones, even at high CV E % values (26.0 to 32.5). Sangalli et al (2004) also found low experimental precision values for DML in studies on fertilization with organic residues and nitrogen. Marco et al (2006) also obtained a high coefficient of experimental variation working with different Citronella Java (Cymbopogon winterianus Jowitt) row spacing and harvesting seasons.…”
Section: Single and Joint Variance Analysesmentioning
confidence: 95%
“…Reproduction is by allogamy, with inflorescences of hermaphrodite flowers, but marked by self-incompatibility and irregular germination of seeds. L. alba shows variability for several morphoagronomic traits (Rufino et al, 2010), including its essential oils, which are products of secondary metabolism. Essential oil is a product obtained from vegetable raw material either by distillation with water or steam, leaves, seeds, flowers or by a mechanical process or by dry distillation.…”
Section: Introductionmentioning
confidence: 99%
“…(Azevedo et al, 2012) e abóbora (Cucurbita moschata Duchesne) (Ferreira et al, 2016), por exemplo. Para característica de comprimento do maior broto, a relação entre e foi inversa às demais características, ou seja, há maior peso da componente genética na variação fenotípica total para esta variável, o que também foi observador para comprimento de brotos por Rufino et al (2010) em Lippia alba (ervacidreira-brasileira), mas não para comprimento da rama principal em abóbora (Ferreira et al, 2016).…”
Section: Parâmetros Genéticosunclassified
“…Em couve, Azevedo et al (2012) observaram uma para número de brotos igual a 30,54% frente aos 7,8% observados aqui para P. aculeata. Mesmo para a característica comprimento do broto, cuja foi de alta magnitude, os valores observados foram inferiores ao observado, por exemplo, em L. alba para Rufino et al (2010), em que foi superior a 95% em comparação aos 55% aqui observados.…”
Section: Parâmetros Genéticosunclassified